El Excentrico, 1964-10-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
October 20, 1964 [5 de octubre de 1964]. Ano 15, No 1. Cover has photographs of people setting up for El Excentrico's 14th anniversery celebrations. The headline reads, "Testamonial Dinner - Dance plans being made for Excentrico's 15th Anniversary."